Impact of youth sports specialisation on career and task-specific athletic performance: a systematic review following the American Medical Society for Sports Medicine (AMSSM) collaborative research network`s 2019 youth early sport specialisation summit - Kliethermes, S. A.; Nagle, K.; Côté, J.; Malina, R. M.; Faigenbaum, A.; Watson, A.; Feeley, B.; Marshall, S. W.; LaBella, C. R.; Herman, D. C.; Tenforde, A.; Beutler, A. I.; et al. (British Journal of Sports Medicine, 2020)
The impact, positive or negative, of youth sport specialisation (YSS) on short-term and long-term performance is not fully understood; however, the desire to maximise performance goals is generally considered the primary reason children and adolescents specialise at a young age. We performed a systematic review of original research to establish the association of YSS and task-focused or career-focused performance outcomes.